Understanding Revisit Intention During Covid-19: A Protection Motivation Theory Perspective - Indra Sakti; Dewi Trirahayu; Amelia Oktrivina (Fakultas Ekonomi dan Bisnis, Universitas Tarumanagara, 2023)
This study aims to empirically investigate the influence of destination image, visitor image congruity, and perceived related health issues on revisit intention and the role of perceived risk as moderators in these relationships. We integrated the theory of self-congruity and protection motivation theory to understand post-pandemic travel behaviour further. Using a moderated regression analysis (MRA), data are collected from 402 students from two universities in Jakarta. The results from the study provide that destination image and image congruity are positively related to revisiting intention, while perceived risk has a negative direction. Moreover, perceived risk is essential in the relationship between destination image, image congruity, and revisit intention. These results extend a model for predicting travel behaviour in crisis/pandemic situations, corroborating the earlier studies, and providing practical implications for stakeholders and tourism area managers.